Random Attractors for the Stochastic Discrete Long Wave-Short Wave Resonance Equations - Jie Xin; Hong Lu (Journal of Applied Mathematics)
We prove the existence of the random attractor for the stochastic discrete long wave-short wave resonance equations in an infinite lattice. We prove the asymptotic compactness of the random dynamical system and obtain the random attractor.